Listeria monocytogenes Sequence Types 121 and 14 Repeatedly Isolated Within One Year of Sampling in a Rabbit Meat Processing Plant: Persistence and Ecophysiology - Pasquali, Frédérique; Palma, Federica; Guillier, Laurent; Lucchi, Alex; De Cesare, Alessandra; Manfreda, Gerardo (Frontiers in Microbiology, 2018)
Listeria monocytogenes is a foodborne pathogen adapted to survive and persist in multiple environments. Following two previous studies on prevalence and virulence of L. monocytogenes ST121 and ST14 repeatedly collected in a the same rabbit-meat processing plant, the research questions of the present study were to: 1) assess persistence of L. monocytogenes isolates from the rabbit-plant; 2) select genes associated to physiological adaptation to the food-processing environment; 3) compare presence/absence/truncation of these genes in newly sequenced and publicly available ST121 and ST14 genomes. A total of 273 draft genomes including ST121 and ST14 newly sequenced and publicly available draft genomes were analyzed. Whole-genome Single Nucleotide Polymorfism (wgSNP) analysis was performed separately on the assemblies of ST121 and ST14 draft genomes. SNPs alignments were used to infer phylogeny. A dataset of L. monocytogenes ecophysiology genes was built based on a comprehensive literature review. The 94 selected genes were screened on the assemblies of all ST121 and ST14 draft genomes. Significant gene enrichments were evaluated by statistical analyses. A persistent ST14 clone, including 23 out of 27 newly sequenced genomes, was circulating in the rabbit-meat plant along with two not persistent clones. A significant enrichment was observed in ST121 genomes concerning stress survival islet 2 (SSI-2) (alkaline and oxidative stress), qacH gene (resistance to benzalkonium chloride), cadA1C gene cassette (resistance to 70 mg/l of cadmium chloride) and a truncated version of actA gene (biofilm formation). Conversely, ST14 draft genomes were enriched with a full-length version of actA gene along with the Listeria Genomic Island 2 (LGI 2) including the ars operon (arsenic resistance) and the cadA4C gene cassette (resistance to 35 mg/l of cadmium chloride). Phenotypic tests confirmed ST121 as a weak biofilm producer in comparison to ST14. In conclusion, ST121 carried the qacH gene and was phenotypically resistant to quaternary ammonium compounds. This property might contribute to the high prevalence of ST121 in food processing plants. ST14 showed greater ability to form biofilms, which might contribute to the occasional colonization and persistence on harborage sites where sanitizing procedures are difficult to display.